An index to new species of Nematoda in Zootaxa from 2003 to 2006 - Zhao, Zeng Qi (Zootaxa, 2007)
From 2003 to 2006, 17 papers describing 39 new species were published in Zootaxa by 38 authors from 13 countries. A bibliographic analysis of these papers and a list of the new taxa of Nematoda are presented in this paper.